In the middle of the way there were some wars: exiles, memories and images in the relationships between Italy and the former Yugoslavia - Betella, Gabriela Kvacek [UNESP] (Univ Estadual Paulista-unesp, 2016)
Taking as reference two historical events of the 20th century, the Second World War and the Balkan conflicts that led to the disintegration of the former Yugoslavia, this work assembles some inferences about the condition of exile in the contemporaneity by means of observations on two literary works written in Italian: the novel Materada by Fulvio Tomizza and the memoirs by Elvira Mujcic, Al di la de caos. Separated by almost fifty years, the facts they refer to and their accounts can be analysed as reality and representation of the atrocities that shake us even today. Nevertheless, the novel and the memoirs can also be seen as testimonies that are made by well-thought discontinuities, as if the literary text could contain, in the dislocation between form and content, in both cases, solutions to the representation of moments capable of unsettling the memory of the past and the links with the present, keeping the voices decided to resist.
Keywords: Fulvio Tomizza; Elvira Mujcic; Exile; Memory